2016
DOI: 10.2214/ajr.15.14664
|View full text |Cite
|
Sign up to set email alerts
|

JOURNAL CLUB: Incidence of Complications Following Fluoroscopically Guided Lumbar Punctures and Myelograms

Abstract: Fluoroscopically guided dural punctures result in few complications compared with lumbar punctures performed without fluoroscopic guidance. Postprocedural bed rest greater than 2 hours does not reduce complication rates for fluoroscopically guided lumbar punctures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 14 publications
1
30
3
Order By: Relevance
“…While our post-LP headache rate was higher compared with the study of Rodriguez et al 24 (which contained a higher number of healthy patients), our complication rate with TFLP was lower than that for interlaminar LP compared with the study by Haché et al (containing only patients with SMA). 11,24 While there is evidence that cutting needles, such as the Quincke needles used in our study, lead to a higher rate of post-LP headache, the rate of headache requiring an epidural blood patch is not significantly different between the Quincke needle and nontraumatic needles. 26,27 The study by Rodriguez et al 24 demonstrated that it is possible to obtain a very low rate of headache despite using Quincke needles.…”
Section: Safetycontrasting
confidence: 82%
See 1 more Smart Citation
“…While our post-LP headache rate was higher compared with the study of Rodriguez et al 24 (which contained a higher number of healthy patients), our complication rate with TFLP was lower than that for interlaminar LP compared with the study by Haché et al (containing only patients with SMA). 11,24 While there is evidence that cutting needles, such as the Quincke needles used in our study, lead to a higher rate of post-LP headache, the rate of headache requiring an epidural blood patch is not significantly different between the Quincke needle and nontraumatic needles. 26,27 The study by Rodriguez et al 24 demonstrated that it is possible to obtain a very low rate of headache despite using Quincke needles.…”
Section: Safetycontrasting
confidence: 82%
“…23 Younger age and female sex have been identified as significant risk factors, and these patients are more likely to receive an epidural blood patch. 23,24 The incidence of post-LP headache varies between 2.2% and 32% with different techniques and instrumentation. [23][24][25] Rodriguez et al 24 reported post-LP headache in 2.2% of 2141 patients who underwent fluoroscopy-guided lumbar puncture using either a 22-or 25-ga Quincke needle.…”
Section: Safetymentioning
confidence: 99%
“…Twenty‐eight studies, published between 1970 and 2016 (references in this paragraph resulted from the systematic literature review, Table 3), compared the performance and complications of different diameters of needles. No differences were detected in six studies comparing different needle diameters [47–52], whereas one study concluded that needles with a larger diameter (≤22G) had a positive effect on collection time and resulted in less failures [53]. The LP feasibility study performed in memory clinic settings did not show that large‐bore diameter needles confer independent risk compared with small bore needle types.…”
Section: Resultsmentioning
confidence: 97%
“…Acutely, the most common manifestation of accidental puncture of the CM is patient headache (Cauley, 2015;Rodriguez et al, 2016). Several other clinical stigmata include foot drop, urinary symptoms (Reynolds, 2001;Ahmad et al, 2006), or fasciculations, tremors, pain, and parasthesias in the setting of cauda equina or CM syndrome (Melloni et al, 2015).…”
Section: Accidental Needle Puncture and Damage Of The CMmentioning
confidence: 99%